Improving Teacher Performance: An Overview of Supervisory Behavior in Artistic Supervision - Marno, Marno; Ghoffar, Muhammad Abdul; Fitriah, Nurlaeli (JURNAL AL-TANZIM, 2024)
The phenomenon of conflict resistance between teachers and educational supervisors has been increasingly prevalent lately, manifesting as feelings of low self-confidence and apprehension among teachers when a supervisor or school monitor is about to conduct supervision. The relationship between teachers and educational supervisors should ideally be harmonious in the pursuit of national educational goals. This research seeks to explore the urgency, steps, and implementation models of artistic supervision in efforts to enhance teacher performance. Research data were gathered through observations of academic supervision activities, interviews with supervisors and teachers, document analyses on educational supervision, and the mechanism of implementing educational supervision using an artistic approach. The research findings indicate that the implementation of artistic supervision is a crucial approach in improving teacher performance, alongside the necessary steps and models of artistic supervision implementation. The study concludes that the urgency of artistic supervision must be recognized to break the hereditary culture of teachers' misconceptions about supervisors and the inaccuracies in the supervisors' approach. Awareness of this needs to be continually cultivated by each party, fostering positive reinforcement and a humanistic educational supervision model between the supervisor and supervisee.